Ovarian stimulation for fertility treatments and risk of breast cancer: a matched cohort study. Issue 3 (6th December 2021) - Machtinger, R; Fallach, N; Goldstein, I; Chodick, G; Schiff, E; Orvieto, R; Mashiach, R
Abstract: STUDY QUESTION: Is there a difference in the breast cancer risk among women who underwent ART treatments compared to those who underwent medically assisted reproduction (MAR) infertility treatments or women of reproductive age in the general population? SUMMARY ANSWER: The risk of breast cancer among women treated by ART was similar to the risk among women treated by MAR and women who did not undergo fertility treatments. WHAT IS KNOWN ALREADY: Studies investigating breast cancer risk in women who have undergone fertility treatments have provided conflicting results. STUDY DESIGN, SIZE, DURATION: A retrospective, population-based cohort study included women who underwent ART or MAR treatments and women who did not undergo fertility treatments from 1994 to 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women who underwent ART were matched one to one with women who underwent MAR treatments and one to one with woman from the general population of reproductive age, by year of birth and year of first delivery or nulliparity status. MAR women were also matched to ART women by treatment initiation calendar year. All included women were members of Maccabi Healthcare Services. Data regarding demographics, fertility treatments, BRCA mutation and possible confounders were obtained from the computerized database of electronic health records. The incidence of breast cancer after fertility treatments was compared to the matched controls. MAIN RESULTS AND THE ROLE OF CHANCE: Of 8 25 721 women of reproductive age, 32 366 women who underwent ART were matched with patients treated by MAR (n = 32 366) and 32 366 women of reproductive age. A total of 984 women (1.0%) were diagnosed with breast cancer (mean follow-up period, 9.1 ± 6.3 years; interquartile range [IQR], 3.8–13.7 years). The incidence rates of breast cancer per 10 000 person-years were 11.9 (95% CI, 10.7–13.3), 10.7 (95% CI, 9.6–11.9) and 10.7 (95% CI, 9.6–12.0) in the ART group, MAR group and general population, respectively. The crude risk for breast cancer was similar in the ART group compared with the general population (hazard ratio (HR) = 1.10, 95% CI, 0.94–1.28) and in the ART group compared with the MAR group (HR = 1.00, 95% CI, 0.86–1.16). Further adjustment for age, BMI, smoking, socioeconomic status and parity did not substantially impact the hazard rates for breast cancer (ART vs general population: HR = 1.10, 95% CI, 0.94–1.28; ART vs MAR: HR = 0.99, 95% CI, 0.85–1.16). Among women diagnosed with breast cancer, the prevalence of BRCA1/2 mutations and tumour staging did not differ between the ART, MAR and general population groups. Among women who underwent ART, no correlation was found between breast cancer and the number of ART cycles or the use of recombinant medications or urine-derived medications. LIMITATIONS, REASONS FOR CAUTION: The mean age of women at the end of follow-up was only 42 years thus the study was not powered to detect potential differences in the risk of postmenopausal breast cancer. In addition, we did not sub-classify the exposed patients by the reason for infertility. WIDER IMPLICATIONS OF THE FINDINGS: Breast cancer incidence following ART was comparable to that in the general population or following MAR. Women undergoing fertility treatments and their clinicians may be reassured about the safety of assisted reproduction technologies in terms of premenopausal breast cancer risk. STUDY FUNDING/COMPETING INTEREST(S): No specific funding was used and there are no competing interests. TRIAL REGISTRATION NUMBER: N/A.